Seasonal Cycling of Nitrogen, Phosphorus and Potassium in Isolated Vegetation Mats on an Inselberg in Southwestern Nigeria - Muoghalu, I.; Isichei, A. O. (2014)
On the inselbergs at the University of Ife Campus (7o 31’N, 4o31’E), southwestern Nigeria are mat communities that are completely isolated from each other and have been shown to behave as real islands in their species-area relationships. The amount of nitrogen, phosphorus and potassium in the vegetation and soil of fifteen of these communities on one inselberg were determined bi-monthly through a growing season. These determinations were carried out by randomly selecting three or four mats at a time, clipping all vegetation and excavating the soil on each mat. The excavated soil was sieved to remove subterranean plant material and, after drying, all plant materials and soil were analysed for three elements, nitrogen, phosphorus and potassium. The clippings and excavations were done in March (beginning of rainy season), May, July and September. The concentration of the three elements in the above-ground plant material was highest in May for nitrogen and potassium and in July for phosphorus, and thereafter the concentrations of the three elements declined. Below ground, nitrogen concentration increased continually, phosphorus increased for some time then dropped while potassium was low in May and later increased. The concentration of nitrogen in the soil increased through the season, phosphorus fluctuated while potassium remained more or less constant. The mats could be valuable in understanding nutrient cycling and the relevance of the results obtained from this study is discussed.